Kemampuan Pemecahan Masalah Matematis Ditinjau Berdasarkan Kecerdasan Emosional Siswa Kelas VII SMP - Fransiska Meni Oeleu; Samuel Igo Leton; Aloysius Joakim Fernandez (Program Studi Pendidikan Matematika Universitas Katolik Widya Mandira, 2019)
The research aims to get an overview about the ability of students in solving mathematical problem based on their emotional intelligence. This is qualitative research with a case study design. The subjects of this research were seventh-grade students who has high emotional intelligence, consisting of a student from catholik junior high school in Kefamenanu and one students from state secondary school in Kota Kupang, They were obtained using purposive. The data were collected using a questionnaire of emotional intelligence, a mathematical problem-solving task, and a interview sheet. The analysis of what is obtained from both subjects, being the high crossing of catholik junior high school students Kefamenanu, it is obtained from cross-leg’s ability: students can understand the matter, make quick plans, to implement completion plans and examine back. The state junior high school in Kupang have the ability of low-vang problems acquired from abilities of emerging problems: students cannot understand matter, students are less able to create completion plans and students cannot examine the return settlement sequences